Pengembangan Handout Berbasis Qr Code - Dwi Fitri Winarni (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This study aims to develop handout but that have limited pages which are able to explain the topic broadly through the inclusion of a qr code on special occasions dish materials for traditional events. This research is a research and development (R&D) research that uses the Four-D development model of Thiagarajan and Semmel. The steps involved include define, design, develop, and disseminate. Defining is how to analyze learning, students, concepts, tasks and specifications of learning objectives. Designing is producing a product prototype that will be developed. Developing aims to develop handout prototype based qr code until it is valid and suitable for use. Disseminating is a stage to determine the effectiveness of developing handouts widely distributed. The methods of data collection are through expert validation instruments, observations, interviews, and written test results. The data were analyzed by means of triangulation of sources, techniques, and time. The results showed that based on the validation of IT experts, a score of 39 was obtained at interval 45 > X 37.5, Media Expert obtained a score of 42 located at interval 45 > X 37.5, Material Expert obtained a score of 53 located at interval X 45, subject teacher validation obtained a score of 52 located in the interval X 45, student responses obtained a score of 50.1 located in the interval X 45. Conclusion of research and development results through R & D model 4-D handout based on qr code in the worthy category to be used as a learning medium and able to improve learning achievement.